續斷이 난소적출 흰쥐의 골조직 대사에 미치는 영향 - 김윤수(Yeun Soo Kim); 박원상(Won Sang Park); 김은영(Eun Young Kim); 오현아(Hyun A Oh); 이현삼(Hyun Sam Lee); 손영주(Young Joo Sohn); 손낙원(Nak Won Sohn); 정혁상(Hyuk Sang Jung) (동의생리병리학회지, 2008)
Theosteoporosis, which is occurred after menopause, is a kind of metabolic bone disorder. It develops when the bone mass begins to decrease radically and its main symptoms are the bone fracture and the height-shortening. This thesis aims at what effects the Phlomis umbrosa will have for the prevention of the osteoporosis in the SD-rat that is caused by the ovariectomy. The 24 female white rats, after their ovaries are removed, were divided into the Normals, the Control group, Phlomis umbrosa Administrated group. After then, for 8 weeks, D.W to the normals and the control, and the Phlomis umbrosa(46 mg/100 g) to the Phlomis umbrosa group were given in the mouths of them. After 8 weeks the rats were sacrificed. And the weight, albumin, AST, ALT, total-cholesterol, triglyceride, P, Ca, T4, estradiol, the weight of the femur, the amount of tibia ash, the area of trabecular bone, the thickness of trabecular bone were measured. The serum analysis shows that the total cholesterol of the Phlomis umbrosa Administrated group reduced remarkably, compared to that of the control group. AST, ALT, ALP, T4 of Phlomis umbrosa group were decreased, but not in distinct measure. Estradiol of Phlomis umbrosa group increased substantially compared to that of the control group, but albumin, triglyceride, Phosphorous, calcium of the group showed the tendency to increase, but not so remarkably. The histological observation shows that the area and the thickness of (trabecular bone), the number of osteoclast of the Phlomis umbrosa groups increased significantly compared to those of the control group. Conclusions: The above experiment shows that Phlomis umbrosa has the prevention effect by supplying estradiol. KCI Citation Count: 0